Inheritance of scald resistance in four barley landraces - G. S. Konovalova; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Background. Scald (caused by Rhynchosporium secalis (Oudem.) J.J. Davis) is one of the most harmful barley diseases. The pathogen is characterized by the differential interaction with the host plant genotypes. Therefore, the most rational plant breeding strategy should envisage broadening of genetic diversity of cultivated varieties. It has been found that the majority of the recently released barley varieties and of the previously identified sources of resistance to R. secalis are now susceptible to the pathogen. Only the resistance gene Rrs9 maintains efficiency against the pathogen populations in the Russian Northwest. Earlier, we have found scald resistant barleys to be frequent among barley landrace accessions. It was demonstrated by the hybridological analysis that accessions k-3307, k-15868, k-18989 and k-3481 are protected by effective scald resistance genes that differ from each other, and which are not allelic to the Rrs4, rrs6, rrs7 or Rrs9 genes. The goal of the present work was to study genetic control to the dangerous pathogen in four other barley landraces.Materials and methods. The inheritance of scald resistance was analyzed in barley accessions k-16233, k-27205 (China), k-27768 (India) and k-22299 (Ecuador). The study employed two experimental techniques, that is, the pathogen/host plant differential interactions analysis in the lab, and the hybridological analysis in the field. The experiments were carried out using R. secalis isolates and clones from the pathogen populations sampled in the North Caucasus and the Russian Northwest. Resistance was scored against the scales from 0 (no symptoms) to 4 points (in the lab), and from 0 to 5 points (in the field). Plants that scored 0-2 points were regarded as resistant.Results and conclusions. The analysis of the pathogen clone/host plant interaction has shown that the landraces k-16233, k-27205 (China), k-27768 (India) and k-22299 (Ecuador) are protected by effective genes of scald resistance which differ from each other and are non-allelic to the previously effective genes Rrs4, rrs6, rrs7 and the currently effective Rrs9. According to the hybridological analysis data, k-27205 has one dominant gene of scald resistance; k-16233, k-27768 and k-22299 are protected by two dominant effective resistance genes, all of which manifest themselves at all the stages of plant ontogenesis.